Peran UPTD PPA dalam Upaya Pencegahan Kekerasan Seksual terhadap Perempuan dan Anak di Kabupaten Pohuwato - Dewinta Rizky R. Hatu; Sahrain Bumulo; Rahmat Ladiku (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2026)
Sexual violence against women and children remains a complex social issue requiring not only legal responses but also preventive efforts implemented through local protection institutions. This study analyzes the role of the Regional Technical Implementation Unit for Women and Child Protection (UPTD PPA) in preventing sexual violence in Pohuwato Regency. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation and analyzed using Talcott Parsons’ AGIL framework. The findings indicate that UPTD PPA has strengthened preventive efforts through diversified reporting mechanisms, cross-sector coordination, and community-based educational outreach. However, differences in social structures between sub-districts influence the effectiveness of implementation, revealing an imbalance between structural capacity and social integration. The study highlights that strengthening institutional roles alone is insufficient without alignment between formal protection mechanisms and local social norms. This research contributes to the understanding of local protection systems by demonstrating how the balance of social system functions at the sub-district level shapes the sustainability of sexual violence prevention efforts.